Fabrication of chitosan/gallic acid 3D microporous scaffold for tissue engineering applications. Issue 4 (28th December 2015) - Thangavel, Ponrasu; Ramachandran, Balaji; Muthuvijayan, Vignesh
Abstract: This study explores the potential of gallic acid incorporated chitosan (CS/GA) 3D scaffolds for tissue engineering applications. Scaffolds were prepared by freezing and lyophilization technique and characterized. FTIR spectra confirmed the presence of GA in chitosan (CS) gel. DSC and TGA analysis revealed that the structure of chitosan was not altered due to the incorporation of GA, but thermal stability was significantly increased compared to the CS scaffold. SEM micrographs showed smooth, homogeneous, and microporous architecture of the scaffolds with good interconnectivity. CS/GA scaffolds exhibited approximately 90% porosity on average, increased swelling (600–900%) and controlled biodegradation (15‐40%) in PBS (pH 7.4 at 37°C) with 1 mg/mL of lysozyme. CS/GA scaffolds showed 2‐4 fold decrease in CFUs ( p  < 0.05) for both gram positive and gram negative bacteria compared to the CS scaffold. Cytotoxicity of these scaffolds was evaluated using NIH 3T3 L1 fibroblast cells. CS/GA 0.25% scaffold showed similar viability with CS scaffold at 24 and 48 h. CS/GA scaffolds (0.5–1.0%) showed 60–75% viability at 24 h and 90% at 48 h. SEM images showed that an increased cell attachment was observed for CS/GA scaffolds compared to CS scaffolds. These findings authenticate that CS/GA scaffolds were cytocompatible and would be useful for tissue engineering applications. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 750–760, 2016.